(untitled) (Revista Inclusiones, 2020)
One of the modern approaches to improving the quality of education in universities and organizing more effective interaction between all the participants of the educational process can be the use of distance learning support systems and electronic courses developed based on them, as well as on Internet and cloud services. The latter is a promising area that is rapidly developing and widespread; it opens up new opportunities and means for the development of distance learning. The article justifies the relevance of using cloud services for peer-to-peer interaction and discusses the features of using cloud technologies in education. A comparison of distance learning technologies and cloud technologies has been carried out, based on an expert survey. Cloud services, as well as the ways of spreading peer-to-peer interaction, have been identified and analysed, with the help of which peer learning can be implemented.